The effect of extremly low frequency magnetic fields on membrane potential of lymphocytes - MEGA TİBER, PINAR (My University, 2008)
Objective: Although previous studies demonstrated that extremly low frequency magnetic fields (ELFEMF) affected biologic systems, the mechanisms have not been elucidated yet. However, it is accepted that the interaction must involve the physicochemical properties of the plasma membrane. This study aimed to determine the probable change in membrane potential of mitogen induced lymphocytes exposed to ELFEMF and correlate it with changes in proliferation of exposed cells.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; ELF-EMF; Membrane Potential; Hyperpolarization; ELECTROMAGNETIC-FIELDS; CANCER; EXPOSURE; CELLS